Model For Preparing Teaching Materials And Student Worksheets - Anam, Ahmad Gautsul; Sari, Ni Kadek Wahyuni Merta; Arifin, Ernaldo Fikrul; Supriadin, Supriadin (Abdi Masyarakat, 2025)
Model of Developing Teaching Materials and Student WorksheetsThis community service activity aims to provide training and assistance to lecturers in developing quality teaching materials and student worksheets. The main problem faced by educational institutions is the lack of structured and innovative teaching materials that can facilitate independent learning. The method used includes training workshops, mentoring sessions, and direct practice in developing teaching materials. The results show that participants are able to design teaching materials that are more systematic, interactive, and aligned with learning outcomes. This activity makes a significant contribution in improving the quality of learning and lecturer competence in preparing teaching materials that are in accordance with the needs of students and curriculum demands.